Three-Dimensional-Printed Models: A Novel Approach to Ultrasound Education of the Placental Cord Insertion Site - Samantha Ward; Sharon Maresse; Zhonghua Sun (Applied Sciences)
Assessment of the placental cord insertion (PCI) is a vital component of antenatal ultrasound examinations. PCI can be complex, particularly in cases of abnormal PCI, and requires proficient sonographer spatial perception. The current literature describes the increasing potential of three-dimensional (3D) modelling to enhance spatial awareness and understanding of complex anatomical structures. This study aimed to evaluate sonographers’ confidence in ultrasound assessment of the PCI and the potential benefit of novel 3D-printed models (3DPMs) of the PCI in ultrasound education. Sonographers employed at a large private medical imaging practice in Western Australia were invited to participate in a face-to-face presentation of two-dimensional (2D) ultrasound images, ultrasound videos, and 3DPMs of normal cord insertion (NCI), marginal cord insertion (MCI), and velamentous cord insertion (VCI). Our objective was to determine the benefit of 3DPMs in improving sonographers’ confidence and ability to spatially visualise the PCI. Thirty-three participants completed questionnaires designed to compare their confidence in assessing the PCI and their ability to spatially visualise the anatomical relationship between the placenta and PCI, before and after the presentation. There was a significant association between a participant’s year of experience and their confidence levels and spatial awareness of the PCI prior to the demonstration. The results showed the 3DPMs increased participant confidence and their spatial awareness of the PCI, with no significant association with years of experience. Additionally, participating sonographers were asked to rate the 3DPMs as an educational device. The 3DPMs were ranked as being a more useful educational tool for spatially visualising the NCI, MCI, and VCI than 2D ultrasound images and videos. Most participants responded favourably when asked whether the 3DPMs would be useful in ultrasound education, with 75.8%, 84.8%, and 97% indicating the models of NCI, MCI, and VCI, respectively, would be extremely useful. Our study has demonstrated a potential role for 3DPMs of the PCI in ultrasound education, supplementing traditional 2D educational resources.